Enhancing research support services in health organizations by implementing a “Research Concierge Desk”, a case study - AlFattani, Areej; AlFirm, Abeer; AlBedah, Norah; AlDakhil, Haifa; Al Muaythir, Elaf; Zeyad, Leena; AlTwaijri, Yasmin (Frontiers in Research Metrics and Analytics, 2024)
Health organizations with teaching and research responsibilities face the need to establish a comprehensive system that addresses the processes and challenges associated with research activities; a system that assists local institutes in becoming research-active by identifying gaps and providing actionable recommendations. The involvement of epidemiologists, biostatisticians, and data scientists is paramount in offering technical and scientific support to health researchers.In our organization, research support services, such as technical, statistical, logistical, and scientific assistance, have been provided to researchers for the past 20 years under the name of "Data Clinic Service". This article discusses the establishment of a physical booth called the "Research Concierge Desk" within a medical center to offer on-site, free-of-charge, and direct consultations to researchers, thereby improving accessibility to data clinic services.The underlying concept of the "Research Concierge Desk" is to align the research workflow for busy clinicians, who require vital assistance in the technical aspects of their research. As well, the desk and its digital platform enabled us to assess research process workflow, such as research submission, data clinic requests, research progress tracking, and researcher satisfaction assessment. We present the initiation of the "Research Concierge Desk" as an innovative solution in hospital settings, outline the available resources, benefits, challenges, and propose areas for improvement.The experience gained from implementing the "Research Concierge Desk" model can greatly benefit other health centers in adopting a similar approach to develop enhanced services for clinical researchers.